Walking cadence required to elicit criterion moderate-intensity physical activity is moderated by fitness status. Issue 17 (2nd September 2019) - Abt, Grant; Bray, James; Myers, Tony; Benson, Amanda C.
ABSTRACT: The aims of this study were to estimate the walking cadence required to elicit a VO2 reserve (VO2 R) of 40% and determine if fitness status moderates the relationship between walking cadence and %VO2 R. Twenty participants (10 male, mean( s ) age 32(10) years; VO2 max 45(10) mL·kg −1 ·min −1 ) completed resting and maximal oxygen consumption tests prior to 7 x 5-min bouts of treadmill walking at increasing speed while wearing an Apple Watch and measuring oxygen consumption continuously. The 7 x 5-min exercise bouts were performed at speeds between 3 and 6 km·h −1 with 5-min seated rest following each bout. Walking cadence measured at each treadmill speed was recorded using the Apple Watch "Activity" app. Using Bayesian regression, we predict that participants need a walking cadence of 138 to 140 steps·min −1 to achieve a VO2 R of 40%. However, these values are moderated by fitness status such that those with lower fitness can achieve 40% VO2 R at a slower walking cadence. The results suggest that those with moderate fitness need to walk at ~40% higher than the currently recommended walking cadence (100 steps·min −1 ) to elicit moderate-intensity physical activity. However, walking cadence required to achieve moderate-intensity physical activity is moderated by fitness status.